Peran Orang Tua dalam Menanamkan Kesetaraan Gender pada Anak Usia Dini di Desa Pelangas Kecamatan Simpang Teritip - Ariesta, Ariesta (ICEJ : Islamic Childhood Education Journal, 2023)
Gender equality must be instilled and performed on children at an early age. This is vital if a child does not block out all that he has. Furthermore, the importance of gender equality in education is not to cause gender bias when the child grows up. In this regard parents have a crucial role in influencing the creation of gender equality values in children. The study aims to find out how parents play a role in instilling gender equality in children of an early age in the garnered demolition village. It is a type of qualitative study using a descriptive approach. The data-collection technique used was observation, interview, and documentation. Data analysis involves three stages of deemed important data reduction, after which you present selected data and can be drawn to a conclusion. Research shows that the role of parents in instilling gender equality in young children in pelangas village is: first, parents give children the opportunity to have equal access to education in both girls and boys and encourage children to engage in home activities regardless of their gender. Second, parents give both girls and boys the opportunity to participate in activities with their friends and to give children the opportunity to participate in society. Third, parents give both girls and boys the responsibility for the child’s choice of decisions and give confidence in both the girl and the boy in controlling the activities of the child himself. Fourth, parents give both girls and boys the opportunity to engage in activities that benefit themselves and others. It may thus be concluded that the results of this study can be used as assessments and images to other parents regarding education that values gender equality for children.